Interleukin-36 is vasculoprotective in both sexes despite sex-specific changes in the coronary microcirculation response to IR injury - El-Awaisi, Juma; Mitchell, Joanne L.; Ranasinghe, Aaron; Kalia, Neena (Frontiers in Cardiovascular Medicine, 2023)
Risks and outcomes of myocardial infarction (MI) are different between men and women and some studies have demonstrated that the latter have a higher risk of mortality. Whilst there are many reasons for this, it may also partially be linked to stronger innate and adaptive immune responses mounted by females compared to males. However, little is known about how sex impacts the coronary microvessels, the site where inflammatory processes take place, after an MI. Intravital and laser speckle microscopy was used to image coronary microvessels and ventricular perfusion in vivo in response to myocardial ischaemia-reperfusion (IR) injury in male and female mice. Interleukin-36 (IL-36) is the latest addition to the IL-1 superfamily of pro-inflammatory cytokines and has recently been shown to mediate inflammation in a number of non-cardiovascular diseases. Its role in mediating potential sex-related microcirculatiory pertubations in the heart are unknown. Therefore, the vasculoprotective efficacy of an IL-36 receptor antagonist (IL-36Ra) was also investigated.Immunostaining and flow cytometry demonstrated higher expression of IL-36 and its receptor in female hearts, an observation confirmed in human samples. Intravital imaging of the anaesthetised mouse beating heart identified significantly greater neutrophil recruitment in female hearts, but a greater burden of thrombotic disease in male hearts. Male mice had reduced functional capillary density and were unable to restore perfusion to baseline values as effectively as females. However, female mice had significantly larger infarcts. Interestingly, IL-36Ra decreased inflammation, improved perfusion, and reduced infarct size in both sexes despite increasing platelet presence in male hearts. Mechanistically, this was explained by IL-36Ra attenuating endothelial oxidative damage and VCAM-1 expression. Importantly, IL-36Ra administration during ischaemia was critical for vasculoprotection to be realised.This novel study identified notable sex-related differences in the coronary microcirculatory response to myocardial IR injury which may explain why some studies have noted poorer outcomes in women after MI. Whilst contemporary MI treatment focuses on anti-platelet strategies, the heightened presence of neutrophils in female IR injured coronary microvessels necessitates the development of an effective anti-inflammatory approach for treating female patients. We also emphasise the importance of early intervention during the ischaemic period inorder to maximise therapeutic effectiveness.